Therapeutic exercises and modalities in athletes with acute hamstring injuries: A systematic review and meta-analysis - Jankaew, A.; Chen, J.-C.; Chamnongkich, S.; Lin, C.-F. (Sports Health: A Multidisciplinary Approach, 2023)
Context: Hamstring strain is a common injury to the lower limbs. Early intervention in the acute phase aids with restoring hamstring function and prevents secondary related injury.